Primary mediastinal large B-cell lymphoma with a rare ALK gene mutation - O. I. Kit; I. A. Kamaeva; I. B. Lysenko; I. A. Novikova; N. N. Timoshkina; N. V. Nikolaeva; Ya. S. Gaisultanova; N. Yu. Khamaneva; A. A. Pushkin (Успехи молекулярной онкологии, 2022)
Introduction. Primary mediastinal large B-cell lymphoma is an aggressive variant of lymphoma characterized by genetic heterogeneity. First-time therapy for primary mediastinal large B-cell lymphoma usually includes immunochemotherapy. However, a substantial proportion of patients do not respond to this therapy.Objective – to analyze clinical characteristics of primary refractory primary mediastinal large B-cell lymphoma taking into account the results of targeted next-generation sequencing (NGS).Materials and methods. A 22‑year-old patient with primary mediastinal large B-cell lymphoma who had not responded to immunochemotherapy was tested using targeted NGS for 77 genes.Results. We identified 2 rare mutations in the ALK gene with an unclear clinical value. According to the literature, these mutations are primarily found in solid tumors.Conclusion. Missense mutations identified in the ALK gene are presumably associated with the course of primary mediastinal large B-cell lymphoma, in particular, with primary refractory disease.